2017
DOI: 10.1002/elps.201600511
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of the performance of Illumina's MiSeq FGx™ forensic genomics system

Abstract: This study assesses the performance of Illumina's MiSeq FGx System for forensic genomics by systematically analyzing single source samples, evaluating concordance, sensitivity and repeatability, as well as describing the quality of the reported outcomes. DNA from 16 individuals (9 males/7 females) in nine separate runs showed consistent STR profiles at DNA input ≥400 pg, and two full profiles were obtained with 50 pg DNA input. However, this study revealed that the outcome of a single sample does not merely de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
6
29
0
Order By: Relevance
“…All markers showed HB ≥ 0.60 (manufacturer's default threshold settings) except for D22S1045 and D5S818 that yielded lower HB values, 0.43 (0.02) and 0.57 (0.02), respectively (Table S6). These findings were in line with earlier studies that reported imbalances at D22S1045 [3, 12-15, 17, 22, 54, 57] and D5S818 [53,54,57]. Six aSTRs (D4S2408, CSF1PO, D7S820, D8S1179, D9S1122 and TH01), one Y-STR (DYF387S1) and three X-STRs (DXS10135, DXS10074 and HPRTB) displayed HB ≥ 0.90 (Table S6).…”
Section: Heterozygous Balancesupporting
confidence: 91%
“…All markers showed HB ≥ 0.60 (manufacturer's default threshold settings) except for D22S1045 and D5S818 that yielded lower HB values, 0.43 (0.02) and 0.57 (0.02), respectively (Table S6). These findings were in line with earlier studies that reported imbalances at D22S1045 [3, 12-15, 17, 22, 54, 57] and D5S818 [53,54,57]. Six aSTRs (D4S2408, CSF1PO, D7S820, D8S1179, D9S1122 and TH01), one Y-STR (DYF387S1) and three X-STRs (DXS10135, DXS10074 and HPRTB) displayed HB ≥ 0.90 (Table S6).…”
Section: Heterozygous Balancesupporting
confidence: 91%
“…Physical characteristics and biogeographical ancestry predictions can provide investigative leads in cases where no information in otherwise available . The ForenSeq™ DNA Signature Prep Kit using Primer Mix B was recently assessed for some performance metrics however, only one of these studies included phenotypic and ancestry predictions in their assessment of UAS (725 individuals tested) and found that ancestry and phenotypic predictions were obtainable for most samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ForenSeq™ Signature Prep Kit has been evaluated for sensitivity, repeatability, allele coverage ratio, concordance with capillary electrophoresis methods, as well as aptitude in handling mixed DNA samples, challenging (degraded) samples, and ancient DNA samples . Additional tests for phenotypic and biogeographical ancestry predictions for 725 individuals from four population groups: Chinese, African American, US Caucasians, and Southwest Hispanics, found that ancestry and phenotype predictions were obtainable for most individual samples and phenotypic estimations were generally concordant with the population .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evaluations of MPS kits and instruments for forensic DNA testing have shown that outcomes are, in general, concordant with CE methods and full profiles could be obtained from as little as 25 to 100 pg DNA. The reports included three HID-Ion AmpliSeq™ Identity Panels (Thermo Fisher Scientific) targeting over 100 identity SNPs (iSNPs) [ 11 13 ], two Ion PGM panels (Thermo Fisher Scientific) testing 10 autosomal STRs ( aSTRs ) [ 14 , 15 ], Promega’s panels testing 17 or 23 STR kits plus amelogenin [ 16 , 17 ], and Illumina’s MiSeq FGx platform testing their Primer Mix A (153 targets/loci, including 27 aSTRs, 24 Y-STRs, 7 X-STRs, and 94 iSNPs plus amelogenin), and/or Primer Mix B (231 loci, including Primer Mix A plus 22 phenotypic and 56 biogeographical ancestry SNPs) [ 18 23 ].…”
Section: Introductionmentioning
confidence: 99%